ʻDER MANN, DEN ICH VERGÖTTERTE, HAT UNS INS UNGLÜCK GEFÜHRTʼ:1 THE POST‐WAR CRISIS OF CONSCIOUSNESS AS MIRRORED IN ESSAYS AND QUESTIONNAIRES BY NUREMBERG'S SCHOOLCHILDREN IN 1946. (October 2016) - Müller, Beate
ABSTRACT: In 1946, Nuremberg's schools inspector Otto Barthel had local schoolchildren write essays on their wartime experiences. They were also asked to fill in questionnaires which specifically addressed their political attitudes. About 3, 000 pupils submitted their work. The texts tell a complex story about the thoughts and feelings of German adolescents in the early post‐war period, demonstrating the ideological influence of National Socialism, trauma suffered during the war, and the shock, frustration, and disorientation after the collapse of the Third Reich. Whilst in many of the questionnaires, the wrongs of National Socialism are clearly identified, the essays tend to be more evasive. They display coping strategies such as idealisation of life before the war, denial, withdrawal from politics altogether, turning to religion for ethical and moral orientation, portraying Germans as victims, relativising German atrocities in the face of Allied military actions and occupation policy, as well as devotion to diligence, hard work, and moral fortitude in order to overcome material deprivation and to regain respect in the world. Although the young pointed to their youth to exonerate themselves from political responsibility, they also inscribed themselves into the conflicted world of adult Germans in a defeated Germany, with their narratives and questionnaire responses already containing many of the discursive tenets of German 'Vergangenheitsbewältigung'. Im Jahre 1946 ließ der Nürnberger Schulrat Otto Barthel die Schüler der städtischen Schulen Aufsätze schreiben über ihre Kriegserlebnisse. Die Kinder hatten auch Fragebögen auszufüllen, die ausdrücklich ihre politischen Einstellungen erkundeten. Rund 3000 Schüler reichten ihre Arbeiten ein. Diese Texte vermitteln ein komplexes Bild von den Gedanken und Gefühlen der deutschen Jugendlichen in der frühen Nachkriegszeit. Sie veranschaulichen den ideologischen Einfluss des Nationalsozialismus, im Krieg erlittene Traumata, sowie den Schock, die Frustration und Desorientierung nach dem Zusammenbruch des Dritten Reichs. Während in vielen Fragebögen die Verfehlungen des Nationalsozialismus klar identifiziert werden, sind die Aufsätze in diesem Punkt meist eher ausweichend. Sie zeigen Bewältigungsstrategien wie Idealisierung der Vorkriegszeit, Verleugnung, Rückzug von der Politik, Hinwendung zur Religion als Sinnstifterin, Darstellung der Deutschen als Opfer, Relativierung deutscher Gräueltaten angesichts militärischer Handlungen und der Besatzungspolitik der Alliierten, sowie eine Hinwendung zu Fleiß, harter Arbeit und moralischer Rechtschaffenheit zwecks Überwindung materieller Not und Wiedergewinnung von Respekt in der Welt. Obwohl die Jugendlichen auf ihre Jugend verwiesen, um sich von politischer Verantwortung zu befreien, schrieben sie sich auch in die konfliktträchtige Welt der Erwachsenen im besiegten Deutschland ein. Ihre Narrative und Fragebogenantworten enthielten bereits viele der diskursiven Topoi deutscher Vergangenheitsbewältigung.